CLINICAL OUTCOMES OF ELECTROSURGERY FOR MANAGEMENT OF GIANT CONDYLOMA ACUMINATA: A SYSTEMATIC REVIEW - Eviani, Fortunia Mona; Stella, Maureen Miracle; Budiyanto, Arief; Pudjiati, Satiti Retno; Alfieri, Alessandro (Folia Medica Indonesiana, 2025)
Giant condyloma acuminata (GCA) is a rare sexually transmitted disease that is locally aggressive with a high recurrence rate. Electrosurgery is a minimally invasive procedure that may be less expensive, quicker, and safer than conventional surgery. This study aimed to review the management of GCA with electrosurgery. We followed PRISMA 2020 guidelines to search and retrieve literature in the following databases: PubMed, ProQuest, Taylor & Francis, ScienceDirect, JSTOR, and SAGE without time restrictions. The study inclusion criteria were original articles that studied the outcome of electrosurgery in GCA. The authors evaluated the risk of bias using the Joanna Briggs Institute (JBI) risk-of-bias assessment. From 572 studies, seven were selected. All studies were published in English between 1997 and 2024. The affected regions in the studies include anal/perianal/anorectal (n=6), vulva (n=2), penis (n=2), scrotal (n=1), vagina (n=1), and suprapubic (n=1). Electrosurgical methods used were electrocautery, electrosection, and electrofulguration, with or without adjunctive treatments. Most cases achieved initial clearance, although one case had a rapid recurrence despite multiple interventions and progressed to squamous cell carcinoma. Recurrence was reported in three cases overall, with timing ranging from weeks to months after treatment. A few adverse effects were infrequent and included a burning sensation during application, minor bleeding, depigmentation, superficial atrophic scarring, and a small remnant ulcer. Electrosurgery demonstrates great potential in treating GCA, particularly when combined with other treatment modalities. However, none of the studies was a randomized controlled trial (RCT). To strengthen the evidence base, RCTs are definitely required.